The Role of Government and Community in Supporting Religious Moderation Programs: A Survey Method - Supandi Supandi; Mujiburrohman; Taufiqurrohman (International Journal of Islamic Thought and Humanities, 2026)
Religious moderation is a trending topic that warrants study and research; however, the issue of understanding, actions, obstacles, and improvements, as well as its development, still cannot be measured properly. The purpose of this research is to explore and measure the understanding, actions, obstacles, and improvement, as well as the development of Religious Moderation. This research employs a survey method. The data sources are government employees, the community, and religious leaders in Madura. The results show that government employees, in supporting Religious Moderation, are 65% (neutral position). Meanwhile, in the realm of Action, there is up to 66.6% agreement with the concept of Religious Moderation. Among the obstacles to the implementation of Religious Moderation, there is a 65% figure in the preparation of the Religious Moderation strategy. The increase in the role of government employees in implementing Religious Moderation indicates that 67% falls within the realm of development. The development of Religious Moderation research shows that the subjects of Religious Moderation are students, the community, and the PAI curriculum, whereas current research focuses on government employees and the Religious Moderation program. This research provides a basis for government policymaking to design the Religious Moderation program more effectively.